Epigenetics in rare neurological diseases - Roberts, Chris-Tiann; Arezoumand, Khatereh Saei; Kadar Shahib, Ashraf; Davie, James R.; Rastegar, Mojgan (Frontiers in Cell and Developmental Biology, 2024)
Rare neurological diseases include a vast group of heterogenous syndromes with primary impairment(s) in the peripheral and/or central nervous systems. Such rare disorders may have overlapping phenotypes, despite their distinct genetic etiology. One unique aspect of rare neurological diseases is their potential common association with altered epigenetic mechanisms.Epigenetic mechanisms include regulatory processes that control gene expression and cellular phenotype without changing the composition of the corresponding DNA sequences. Epigenetic factors include three types of proteins, the "readers, writers, and erasers" of DNA and DNA-bound proteins. Thus, epigenetic impairments of many neurological diseases may contribute to their pathology and manifested phenotypes. Here, we aim to provide a comprehensive review on the general etiology of selected rare neurological diseases, that include Rett Syndrome, Prader-Willi Syndrome, Rubinstein-Taybi Syndrome, Huntington's disease, and Angelman syndrome, with respect to their associated aberrant epigenetic mechanisms.